Decolonial STEM Education and the Integration of a Critical Global Citizenship Education Framework in an Ontario Secondary School - Gyamerah, Kenneth; Mao, Jane; Johnston, Alice; Hodges, Ethan; Pillay, Thashika; Pashby, Karen; Butler, Alana (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
This study examines how the HEADSUP framework supports STEM teachers in integrating anti-oppressive and critical social justice frameworks into their teaching. Using a qualitative case study approach, STEM teachers and students at an Ontario secondary school participated in weekly sessions focused on utilizing HEADSUP in their STEM courses. Data were collected through semi-structured interviews with teachers and classroom observations conducted by the research team. Findings reveal both opportunities and challenges in decolonizing STEM education through critical decolonial frameworks. Teacher interviews indicate that integrating HEADSUP into teaching amplified students’ voices, promoted active engagement in lessons, and encouraged them to explore concepts beyond the standard STEM curriculum. Findings also highlight that the implementation of anti-oppressive and social justice frameworks in STEM classrooms is constrained by the current provincial high school STEM curriculum. The study discusses implications for educational policy, particularly the need for curricular reforms that support anti-oppressive approaches in STEM education.